Why Do Firms Pay Bribes? Evidence on the Demand and Supply Sides of Corruption in Developing Countries - Gauthier, Bernard; Goyette, Jonathan; Kouame, Wilfried (World Bank, Washington, DC, 2020)
This paper empirically examines the demand and supply sides of bribery using World Bank Enterprise Survey data on 18,005 firms in 75 developing countries. It assesses the determinants of firms' bribe paying behavior and examine how bribe behavior affects two main sectors where corruption is rampant: taxation and government contracts. The paper shows that corruption in tax administration tends to be mainly a demand-side phenomenon. Paying a bribe requested by a public official is associated with a 16 percent increase in the share firms~^!!^ sales not reported for tax purposes. In public procurement, the results suggest, on the contrary, that corruption is a supply-side phenomenon, with bribe transactions generally initiated by firms to secure public contracts. Firms supplying a bribe without a previous request by officials is associated with a 17 percent increase in the bribe paid to secure a government contract, more than three times the effect observed on the demand side of bribery.